Phytochemicals and biological activity of Tetracera scandens Linn. Merr. (Dilleniaceae): a short review - Nokhala, Ahmed; Siddiqui, Mohammad Jamshed Ahmad (Wolters Kluwer Medknow Publications, 2020)
Tetracera scandens is a southeast Asian shrub that belongs to family Dilleniaceae. Over the years, different parts of the plant have been used for the management of different diseases, including diabetes mellitus, hypertension, rheumatism, diarrhea, hepatitis, and inflammation. This variety of medical indications has attracted the attention of many researchers to this plant species, leading to the conduction of many research studies on different parts of the plant. These studies have confirmed some of the aforementioned activities of the plant, whereas other indications remain to be ascertained. This article is an attempt to summarize the studies conducted on T. scandens and to explore the isolated phytochemicals.